Institutional Pressure and the Adoption of Sustainable Development Goals (SDGs) in Mining Companies in Indonesia - Sammy Rommy Novie Korua; Olivia S. Nelwan; Victor P.K. Lengkong; Rita N. Taroreh; Genita G. Lumintang (SOSIOEDUKASI, 2025)
This study uses institutional theory as the analytical framework to examine how institutional pressures affect the institutional adoption of sustainable development goals (SDGs) among mining companies in Indonesia. Through a qualitative content analysis of sustainability reports from 11 firms in three categories of ownership (state-owned enterprises, multinational corporations, and domestic private firms), this study examines different patterns of SDG integration due to coercive normative and mimetic pressures. The findings reveal that multinationals pursue the widest array of SDGs 15-16, motivated by global ESG expectations and investor demands. State-owned enterprises show moderate adoption of 10-12 goals mainly due to national regulations and the legitimacy of the public. Domestic private firms have high variability in 6-11 goals, with listed or parent-affiliated firms showing more substantive engagement than their smaller non-listed counterparts. Crucially, the research concludes that capital market affiliation, directly or indirectly, serves as a consistent normative force that increases the adoption of SDGs for all ownership types. This research contributes theoretically to the literature, showing that normative pressure from financial markets could outweigh coercive regulatory pressure in driving meaningful sustainability practices in developing economies. Practically, it provides practical insights for regulators, investors, and corporate leaders to enhance the implementation of SDGs beyond mere symbolic disclosure.